MOICANA: Monolithic cointegration of QD-based InP on SiN as a versatile platform for the demonstration of high-performance and low-cost PIC transmitters - Vyrsokinos, K.; Chatzitheocharis, D.; Papadovasilakis, M.; Ketzaki, D.; Calo, C.; Caillaud, C.; Sacchetto, D.; Zervas, M.; Reithmaier, J. P.; Sichkovskyi, V.; Eisenstein, G.; Orenstein, M.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
The integration of optical sources in Si photonic transceivers has relied so far on externally coupled III-V laser dies within the assembly. These hybrid approaches are however complex and expensive, as there are additional cost-increasing factors coming from the redundant testing of the pre- and post-coupled laser photonic chips. Further optimization of Photonic Integrated Circuits (PICs) cost and performance can be obtained only with radical technology advancements, such as the "holy grail" of Silicon Photonics; the monolithic integration of III-V sources on Si substrates. MOICANA project funded by EU Horizon 2020 framework targets to develop the technological background for the epitaxy of InP Quantum Dots directly on Si by Selective Area Growth with the best-in-class, in terms of losses and temperature sensitivity, in a CMOS fab, i.e. the SiN waveguide technology. In addition, MOICANA will develop the necessary interface for the seamless light transition between the III-V active and the SiN passive part of the circuitry featuring advanced multiplexing functionality and a combination of efficient and broadband fiber coupling. Through this unique platform, MOICANA aims to demonstrate low cost, inherent cooler-less and energy efficient transmitters, attributes stemming directly from the low loss SiN waveguide technology and the QD nature of the laser's active region. MOICANA is targeting to exploit the advantages of the monolithic integrated PICs for the demonstration of large volume single-channel and WDM transmitter modules for data center interconnects, 5G mobile fronthaul and coherent communication applications.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Monolithic Integration; Optical Interconnects; Optical Interfaces; Optical Transceivers; Quantum Dot; Quantum Dot Lasers; Silicon Photonics